The development of oxygen content in the Greenland Sea from 1993 to 2008. A study of convection depth and deep layer changes. - Botnen, Helle Augdal (The University of Bergen, 2009)
In previous years the hydrography in the Greenland Sea have been investigated based on temperature and salinity observations along with different transient tracers. In this work annual zonal sections, averaged values of the central parts of the Greenland Sea and the deep layer changes have been investigated to provide a fuller view of the changes and trends in the Greenland Sea over most of the 1990s and 2000s. The main parameter is the oxygen concentration that has been used together with temperature and salinity. Earlier it has been stated that the increase in temperature and salinity is due to the inflow of Arctic Ocean Deep Water in the form of Canadian Basin Deep Water and Eurasian Basin Deep Water, and reduced convection compensating for the increase of these parameters. Investigation of the oxygen concentration has provided another argument to support this theory where the decreasing trend in oxygen along with the increasing trend in temperature and salinity indicate the inflow of a warmer, more saline water mass of older age than the Greenland Sea Deep Water. Master i Geofysikk - Kjemisk oseanografi MAMN-GFKJ GEOFKJEM